SPECIAL EDUCATION SCHOOL LEADER LEADERSHIP IN MALAYSIA - Muhammad Faizal A. Ghania; Shamim Samsuddin (EARR (Educational Administration Research and Review), 2022)
Each school plans to produce quality students who meet the needs of certain aspects: physical, emotional, spiritual, intellectual and social. Thus, the effort to achieve this goal is highly dependent on the competence of school leaders. Yet, some special education school leaders are still lacking in understanding leadership strategies efficiently and effectively. Billingsley, McLeskey, and Crockerr (2018) agree that view by arguing that special education school leaders need to be given training and guidance to lead schools well. The reason is because special education school leaders are still less clear and less prepared to lead schools (Schaff, Williamson Novak, 2015). Further discussion of this presentation focuses on the concept of leadership and the leadership of special education school leaders. This presentation also discusses the scenario of special education schools in Malaysia, the leadership model of special education school leaders as well as the leadership issues of special education schools leaders globally.